The Revolving Door Flap: Revisiting an Elegant but Forgotten Flap for Ear Defect Reconstruction - Golash, Anupam; Bera, Sudipta; Kanoi, Aditya V.; Golash, Abhijit (Indian Journal of Plastic Surgery, 2020)
Background The revolving door flap, although well described in the literature, is not widely used in general plastic surgery practice. The flap has been used for anterior auricular and conchal defects and is considered elegant for its unique flap design and peculiarity of flap harvest. However, due to its use for a very specific purpose and unique flap harvest technique that may be difficult to grasp, the flap is not very popular in reconstructive practice.Objectives This study aims to evaluate the understanding and learning curve of the revolving door flap, assess surgical outcome, and reemphasize its utility and elegance in reconstruction of ear defects.Methodology This is a case series of nine surgeries performed between January 2014 and 2018. Three cases were performed by the senior author and six cases by two junior authors. Patients were observed for complications and aesthetic outcomes.Results The mean dimension of the flaps was 27.22 mm × 22.78 mm. The mean operative time was 56.56 minutes (standard deviation 22.50, standard error of the mean 7.5). Flap congestion was noted in three cases postoperatively which resolved completely by the second week. Major “pinning” of the ear was noted in four cases.Conclusion Though infrequently performed, the revolving door flap has an easy learning curve once the proper harvest technique and flap movement has been grasped. The flap harvest is convenient, safe, and yields predictable results. Not only is total or partial flap loss extremely rare, the flap is sensate, color match is good, auricular contour is maintained, and the donor site can be closed primarily and remains well hidden.
Keywords: ear reconstruction; conchal defect; revolving door flap; subcutaneous pedicle